Analisis Keberhasilan Lebron James Menjadi MVP di Olimpiade Paris 2024 - Muhammad Alfi Zain Waladi Rahimy; Himawan Wismanadi; Hijrin Fithroni; Afif Rusdiawan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Basketball is a dynamic team sport that emphasizes hand coordination, requiring players to score by shooting the ball into the opponent’s hoop. The game involves five players per team and demands mastery of several fundamental technical skills, including throwing and catching, dribbling, shooting, pivoting, and lay-up techniques. One of the highest individual achievements in basketball is being named the Most Valuable Player (MVP), a title awarded to athletes who demonstrate exceptional performance during a game or tournament. This study aims to analyze the determining factors behind an athlete achieving MVP status, specifically focusing on LeBron James from the United States basketball team during the 2024 Paris Olympics final match against France. The research employs a descriptive method with data collection through document analysis, particularly using official match statistics. The assessment includes both physical performance metrics—such as points, rebounds, assists, blocks, steals, turnovers, and fouls—and psychological aspects, such as mental toughness during competition. Statistical data from the match showed that LeBron James recorded 14 points, 6 rebounds, 1 block, 10 assists, 2 steals, 5 turnovers, and 3 fouls. His shooting efficiency was also high, with a 60% field goal percentage (6/10), 62.5% on two-point shots (5/8), 50% on three-point shots (1/2), and 100% on free throws (1/1). The findings indicate that high contributions in both offensive and defensive aspects significantly influence the MVP designation. This study concludes that MVP recognition is strongly supported by measurable statistical performance and recommends that coaches integrate performance analysis technology to maximize athlete potential based on individual needs.